PERILAKU KEPALA DESA DALAM PENDIRIAN PERPUSTAKAAN DESA BANUA UJUNG KECAMATAN EMBALOH HULU KABUPATEN KAPUAS HULU - Nicolaus Purwanto E.42009040 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2018)
Writing this thesis is to describe and analyze the behavior of Village Head founding the Library in Banua Ujung Village. This thesis based on concern rised less effective performance of village head in founding the village library. This research uses descriptive qualitative research types. Research location is in Banua Ujung Village Embaloh Hulu District Kapuas Hulu Regency. Subjects in this study is the secretary of Banua Ujung Village, all of orchard head in Banua Ujung Village, chief of the desk development in Banua Ujung Village, Chief of the desk goverment in Banua Ujung Village, chief of the desk economics Banua Ujung Village, head of Banua Ujung Village Parlement and 3 people of Banua Ujung Village. Conclusion of this study is the behavior of Village Head founding the Library in Banua Ujung Village not optimal, with attitude, ability and motivation indicators. Attitude of village head not fully support the library founding, because do not follow with concrete actions which for succes founding of library. Ability of village lead assumed by less especially related to intellectual ability to make planning and inovation. So also with motivation village lead still assumed to lower because  village head not yet realized about importance of library, nothing incentive, and staff support and also society which still lower. Therefore, the researchers hope the village head change him behavior with change him attitude, improving ability an motivation for a better management of library and can be exploited by people. Keywords: Behavior, Attitude, Ability, Motivation.